OP0065 Long-Term Safety and Effectiveness of Adalimumab in Children with Moderately to Severely Active Polyarticular or Polyarticular-Course Juvenile Idiopathic Arthritis. (9th June 2015) - Ruperto, N.; Brunner, H.; Wallace, C.; Toth, M.; Foeldvari, I.; Bohnsack, J.; Milojevic, D.; Rabinovich, E.; Vavrincova, P.; Kingsbury, D.; Marzan, K.; Quartier, P.; et al.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is one of the most common childhood rheumatic diseases. Adalimumab (ADA) is approved for moderate to severe polyarticular JIA (pJIA) in patients (pts) ≥4 yrs in Australia and Japan and for pts ≥2 yrs in the US and EU. Objectives: To evaluate long-term safety and effectiveness of ADA in pts with moderately to severely active pJIA who are prescribed and treated with ADA in routine clinical practice. Methods: This is an ongoing, multicenter, non-interventional, observational registry of pts with moderately to severely active pJIA who are treated with either ADA ± methotrexate (MTX) or MTX alone as part of their routine clinical care. 800 pts (500 ADA/300 MTX) were to be enrolled in the US, EU, and Australia. The follow-up observational period is 10 yrs from enrollment into one of the treatment arms. Observational adverse events (AEs) were recorded from the first day in the registry through last contact, irrespective of registry treatment duration. Clinical outcomes were assessed by 27-joint juvenile arthritis disease activity score (JADAS27), based on CRP. 5 yr interim data are presented. Results: As of January 2014, enrollment is complete. 842 pts (540 ADA/302 MTX) were treated as of the March 28, 2014 cutoff. Mean pJIA disease duration at enrollment was 1.3 and 3.7 yrs and mean duration of study exposure was 643 and 653 days for MTX and ADA arms, respectively. Baseline mean AJC73 was 5.8 and 5.4 for MTX and ADA, respectively, and CHAQ-DI was 0.6 for both groups. Overall, 153 pts (50.7%) in the MTX arm and 132 pts (24.4%) in the ADA arm discontinued registry drug. Of those, 22 (7.3%) and 23 (4.3%) in the MTX and ADA arm, respectively, discontinued due to an AE, and 39 of the 153 pts in the MTX arm discontinued as they switched to the ADA arm. The observational AEs are summarized (Table ). No deaths, malignancies, or opportunistic infections were reported. In the ADA arm, there were 13 (2.4%) pts with serious infectious AEs (abdominal abscess, acute tonsillitis, appendicitis, cellulitis, gastroenteritis, mononucleosis, viral meningitis, pneumonia, pyelonephritis, scarlet fever, subcutaneous abscess, tonsillitis, urinary tract infection, and varicella). Frequencies and rates of treatment-emergent AEs were similar to those reported for observational AEs. Mean JADAS27 improved from 12.1 at baseline to 9.4, 6.1, 5.1, 4.4 at months 1, 3, 6, and 12 for pts in the MTX arm and from 12.1 at baseline to 7.4, 5.5, 4.4, 4.5 in the ADA arm, respectively (observed data). Conclusions: Overall, ADA is well-tolerated in these pts with active pJIA. No new safety signals were observed, and based on this interim analysis, the known safety profile of ADA remains unchanged. Acknowledgements: AbbVie sponsored the study (NCT00783510 ), contributed with PRINTO and PRCSG to the design, and participated in data collection, analysis, and interpretation, and in the writing, review, and approval of the abstract. Medical writing support was provided by Jessica L. Suboticki, PhD, of AbbVie. Disclosure of Interest: N. Ruperto Employee of: GASLINI Hospital, which has received contributions to support the research activities of the network of PRINTO from AbbVie Inc., AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Eli Lilly and Co., "Francesco Angelini", GlaxoSmithKline, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, and Wyeth Pharmaceuticals. NR has served on speaker's bureau for Astellas, AstraZeneca, Bristol-Myers Squibb, Italfarmaco, Janssen Biologics B.V., MedImmune, Roche, and Wyeth/Pfizer, H. Brunner Consultant for: AbbVie Inc., AstraZeneca, Centocor, Bristol-Myers Squibb, Boehringer-Ingelheim, Pfizer, Regeneron, Hoffman La-Roche, Novartis, UCB, and Genentech, Speakers bureau: Genentech Pharmaceuticals, C. Wallace Grant/research support from: Pfizer, Amgen, Consultant for: Amgen, Novartis, M. Toth: None declared, I. Foeldvari Consultant for: AbbVie, Novartis, J. Bohnsack Consultant for: Novartis, D. Milojevic Consultant for: Genentech, Novartis, E. Rabinovich Grant/research support from: UCB Pharma, Janssen Research & Development, LLC, Hoffmann-La Roche Inc., AbbVie, P. Vavrincova: None declared, D. Kingsbury Grant/research support from: AbbVie, K. Marzan Grant/research support from: AbbVie, P. Quartier Grant/research support from: AbbVie, Novartis, Pfizer, BMS, Chugai-Roche, Medimmune, Servier, Swedish Orphan Biovitrum; Participates on a data management committee of a phase 3 trial by Sanofi, Consultant for: AbbVie, Novartis, Pfizer, BMS, Chugai-Roche, Medimmune, Servier, Swedish Orphan Biovitrum, K. Minden Grant/research support from: Pfizer, Abbvie, Consultant for: Pfizer, Abbvie, Roche/Chugai, Novartis, Medac, Pharm-Allergan, Speakers bureau: Pfizer, Abbvie, Roche/Chugai, Novartis, Medac, Pharm-Allergan, E. Chalom Speakers bureau: AbbVie, G. Horneff Grant/research support from: AbbVie, Pfizer, and Roche and speaker's fees from AbbVie, Novartis, Pfizer, Roche, R.-M. Kuester Grant/research support from: AbbVie, Wyeth/Pfizer, J. Dare Grant/research support from: AbbVie, AstraZeneca, Bristol-Myers Squibb, Horizon Pharma, Medac GmbH, UCB Biosciences, M. Bereswill Shareholder of: AbbVie, Employee of: AbbVie, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie, A. Martini Employee of: GASLINI Hospital, which has received contributions to support the research activities of the network of PRINTO from AbbVie Inc., AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Eli Lilly and Co., "Francesco Angelini", GlaxoSmithKline, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals, Speakers bureau: Astellas, AstraZeneca, Bristol-Myers Squibb, Italfarmaco, MedImmune, D. Lovell Consultant for: AbbVie Inc., AstraZeneca, Centocor, Bristol-Myers Squibb, Pfizer, Regeneron, Hoffman La-Roche, Novartis, UBC, Xoma, Genentech; served on data and safety monitoring boards for Amgen, Forest Research, Speakers bureau: Wyeth Pharmaceuticals